TINJAUAN YURIDIS TERHADAP SENGKETA KEPEGAWAIAN DALAM PUTUSAN PENGADILAN TATA USAHA NEGARA JAKARTA (Studi Terhadap Putusan Nomor: 237/G/2015/PTUN-JKT) - WIWIK ANGGRAINI, S.H NPM. A2021151099, Jurnal Mahasiswa S2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses Juridical Review on Human Resources Dispute in Decision of Jakarta State Administrative Court (Study on Decision Number: 237 / G / 2015 / PTUN-JKT). From the results of this thesis research obtained the basic conclusion In Dispute In Case Number: 237 / G / 2015 / PTUN-JKT. Mangasi Situmeang, S.H., LLM Plaintiff Against the Attorney General of the Republic of Indonesia as Defendant. The Object of Disputes in Case Number: 237 / G / 2015 / PTUN-JKT This Is The Decree of Attorney General of the Republic of Indonesia Number: KEP-IV-551 / C / 08/2015 Date 12 August 2015. Application of Legal Provisions In Case Number : 237 / G / 2015 / PTUN-JKT is the Authority of the State Administrative Court Jakarta In Case Number: 237 / G / 2015 / PTUN-JKT. Based on Article 1 point 9 of the Law of the Republic of Indonesia Number 51 Year 2009 Concerning the Second Amendment to Law of the Republic of Indonesia Number 5 Year 1986 concerning State Administrative Court defines Decision of State Administration is: Decision of State Administration is a written stipulation issued by a state administrative body or officer containing legal action in accordance with applicable, concrete, individual, and final legal rules, which bring legal consequences for a person or a civil legal entity